1999
DOI: 10.1172/jci4236
|View full text |Cite
|
Sign up to set email alerts
|

Reduced angiotensinogen expression attenuates renal interstitial fibrosis in obstructive nephropathy in mice

Abstract: A novel approach was employed to assess the contribution of the renin-angiotensin system (RAS) to obstructive nephropathy in neonatal mice having zero to four functional copies of the angiotensinogen gene (Agt). Two-day-old mice underwent unilateral ureteral obstruction (UUO) or sham operation; 28 days later, renal interstitial fibrosis and tubular atrophy were quantitated. In all Agt genotypes, UUO reduced ipsilateral renal mass and increased that of the opposite kidney. Renal interstitial collagen increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
67
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(74 citation statements)
references
References 46 publications
(66 reference statements)
6
67
0
1
Order By: Relevance
“…This notion is supported by several recent studies using sophisticated experimental approaches by reduction and augmentation of endogenous RAS activities via genomic manipulation of angiotensinogen (Agt) expression in vivo (8,10). In mice lacking Agt, though reduced, renal interstitial fibrosis persists in the complete absence of AngII generation after ureteral obstruction (10). Likewise, interstitial fibrosis in UUO mice with Agt duplication (fourcopy) is not further exacerbated (10).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This notion is supported by several recent studies using sophisticated experimental approaches by reduction and augmentation of endogenous RAS activities via genomic manipulation of angiotensinogen (Agt) expression in vivo (8,10). In mice lacking Agt, though reduced, renal interstitial fibrosis persists in the complete absence of AngII generation after ureteral obstruction (10). Likewise, interstitial fibrosis in UUO mice with Agt duplication (fourcopy) is not further exacerbated (10).…”
Section: Discussionmentioning
confidence: 92%
“…Because the dose of losartan given is sufficient for functionally blocking AT 1 receptor (7,38), these results likely highlight a partial contribution of the RAS to the pathogenesis of chronic renal fibrosis. This notion is supported by several recent studies using sophisticated experimental approaches by reduction and augmentation of endogenous RAS activities via genomic manipulation of angiotensinogen (Agt) expression in vivo (8,10). In mice lacking Agt, though reduced, renal interstitial fibrosis persists in the complete absence of AngII generation after ureteral obstruction (10).…”
Section: Discussionmentioning
confidence: 95%
“…[1][2][3] The intrarenal renin-angiotensin system (RAS) was described in the 1980's, 4 and the kidney contains angiotensin II at a significantly higher level than serum. 5 Although the intrarenal RAS may be altered in some diseased states, 6 -12 the localization of each component of the RAS, such as angiotensin II type 1 and type 2 receptors (AT 1 R and AT 2 R), renin (REN), angiotensinogen (AGTN), and angiotensin-converting enzyme (ACE), in the fibrosing kidney is undefined.…”
mentioning
confidence: 99%
“…These models are predominantly postnatal models with much of the work focused on the role of the proximal convoluted tubule and on late time points in which the interstitial and fibrotic responses predominate. [17][18][19][20] Although early changes in tubular hydrodynamics, tubular dilatation, and medullary injury have been briefly described following obstruction, our knowledge of the contributions of these factors and the potential cellular responses they invoke is lacking.We have previously demonstrated that the distal nephron, including the collecting duct, has an important role in the pathogenesis of obstruction in the fetal human and primate kidney. 1-3 Here, we demonstrate that despite the postnatal nature of the mouse UUO model, this model replicates many of the key pathogenic features of fetal obstruction, making it a suitable and powerful model for investigating early medullary and distal nephron injury.…”
mentioning
confidence: 99%
“…These models are predominantly postnatal models with much of the work focused on the role of the proximal convoluted tubule and on late time points in which the interstitial and fibrotic responses predominate. [17][18][19][20] Although early changes in tubular hydrodynamics, tubular dilatation, and medullary injury have been briefly described following obstruction, our knowledge of the contributions of these factors and the potential cellular responses they invoke is lacking.…”
mentioning
confidence: 99%